Plea agreements in abbreviated process, from technical point of view and the perspective of convicted people: Results from a research on its application in Uruguay (Delito y Sociedad, 2023)
The accusatory criminal reform implemented since November 2017 in Uruguay introduced the institute of plea bargaining. This is a mechanism to reach conviction without a trial where the accused person, with the advice of his defense attorney, agrees on the facts and background of the investigation with the Prosecutor's Office in exchange for some benefit. In the case of Uruguay, the abbreviated process accounts for more than 80% of total prosecuted cases. However, the mechanism has received critics. One of the main ones is the fact that negotiation leads to accepting sentences without the accused having sufficient information, or without the judges adequately controlling them. The specific objectives of this research have been to explore the perception that the convicted have regarding the negotiation process, their opinion on the adequacy of the agreement, and the reasons they had for accepting it, as well as to evaluate the quality of the agreements from a technical point of view. For this, the object of study was approached from a quantitative and qualitative perspective through the analysis of the audio recordings of the hearings in which the agreements were approved, and semi-structured interviews with convicts sentenced in abbreviated processes. The results of the investigation throw up a series of elements for the discussion about these mechanisms in criminal justice, among them: the administratization of criminal justice; the lack of information; the hostile context of the detention; the right to counsel; among others.